Rapid osteoinduction of human adipose-derived stem cells grown on bioactive surfaces and stimulated by chemically modified media flow - Karolina Truchan; Barbara Zagrajczuk; Katarzyna Cholewa-Kowalska; Anna Maria Osyczka (Journal of Biological Engineering)
Abstract Adipose-derived stem cells (ASCs) provide an ample, easily accessible source of multipotent cells, an alternative to bone marrow-derived stromal cells (BMSCs), capable of differentiating into osteoblasts. However, the osteogenic potential of ASCs is reportedly lower than that of BMSCs and protocols to effectively differentiate ASCs into osteoblasts are in high demand. Here, we present novel strategies for effective osteogenic differentiation of human ASCs by combining their culture on bioactive growth surfaces with their treatment with specific supplements in osteogenic medium and application of fluid shear stress. Human ASCs were cultured on PLGA-based composites containing 50 wt% sol-gel bioactive glasses (SBGs) from the SiO2-CaO±P2O5 system, either unmodified or modified with 5 wt% ZnO or SrO. The osteogenic medium was supplemented with recombinant human bone morphogenetic protein 2 (BMP-2), MEK1/2 kinase inhibitor (PD98059) and indirect Smurf1 inhibitor (Phenamil). Fluid shear stress was applied with a standard horizontal rocker. ASC culture on SBG-PLGA composites along with the osteogenic medium supplements enhanced the expression of both early and late osteogenic markers. Modification of SBG with either SrO or ZnO further enhanced osteogenic gene expression compared to ASCs cultured on composites containing unmodified SBGs. Notably, the application of fluid shear stress synergistically strengthened the osteogenic effects of bioactive composites and medium supplements. We also show that the presented culture strategies can drive ASCs toward osteoblastic cells in a 3-day culture period and provide mineralizing osteoblasts through a short, 7-day ASC preculture on bioactive composites. Our results also indicate that the applied osteogenic treatment leads to the phosphorylation of β-catenin and CREB or the COX-2 expression. We believe the presented strategies are feasible for rapid ASC differentiation to early osteoblasts or mineralizing osteoblastic cells for various potential cell-based bone regeneration therapies. Graphical Abstract